دراسة تاثير المستخمص المائي والكحولي لبذور الحرمل ومخاريط السرو في حيوية الرؤيسات االولية لممشوكة الحبيبية granulosus Echinococcus خارج الجسم الحي. - الشنوي فوزية احمد; باقر نور نهاد (Al-Nahrain Journal of Science, 2011)
This study included the preperation of the aquatic extracts of Peganum harmala seeds and cones of Cupressus sempervirens at concentrations (10, 20 or 30) mg/ml and (50, 100 or 200) mg/ml respectively and alcoholic extracts of the seeds P. harmala and cones C.sempervirens at concentrations (1, 2 or 3) mg/ml and (50, 100 or 200) mg/ml respectively. The influence of plant extracts on the percentage of vitality of the protoscolices of Echinococcus granulosus In vitro for the purpose of arriving to the active concentration in killing of protoscolices during the shortest period of time possible as the vitality of protoscolices had caused complete death at the time 30 minute when using the aquatic extracts of seeds P. harmala and cones C. sempervirens at the concentration 30,200 mg/ml respectively. the alcoholic extracts of seeds P. harmala and cones C. sempervirens at concentrations 3,200 mg/ml these had differ to be distinguished with higher inhibition on the vitality of protoscolices and shown complete killing of protoscolices at the time zero minute .